2023
DOI: 10.1038/s41598-023-39126-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between urinary caffeine and caffeine metabolites and stroke in American adults: a cross-sectional study from the NHANES, 2009–2014

Abstract: This study investigates the potential correlation between urinary caffeine levels and the occurrence of stroke, a serious cerebrovascular disease that can lead to disability or death. The data used in this study was obtained from the National Health and Nutrition Examination Survey conducted between 2009 and 2014. The study analyzed a total of 5,339 individuals, divided into a control group (n = 5,135) and a stroke group (n = 162). The researchers utilized multiple logistic regression and smoothed curve fittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
2
1
Order By: Relevance
“…Among the metabolites that contribute to increased risk of IS, 5acetylamino-6-formylamino-3-methyluracil is a caffeine metabolite (Birch Kristensen et al, 2018). However, caffeine has neuroprotective effects and can also regulate stroke risk factors such as blood glucose and lipid levels (Fan et al, 2023). This finding seems contradictory to our study results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Among the metabolites that contribute to increased risk of IS, 5acetylamino-6-formylamino-3-methyluracil is a caffeine metabolite (Birch Kristensen et al, 2018). However, caffeine has neuroprotective effects and can also regulate stroke risk factors such as blood glucose and lipid levels (Fan et al, 2023). This finding seems contradictory to our study results.…”
Section: Discussioncontrasting
confidence: 99%
“…This involves gradually removing individual single SNP and calculating the Meta effect of the remaining SNPs. We observe whether the results change after removing each SNP to determine if the results are influenced by any specific SNP (Feng et al, 2022;Zhang et al, 2023). Horizontal pleiotropy was evaluated based on the Egger intercept, and if p > 0.05, it was considered to have no horizontal pleiotropy (Cai et al, 2022).…”
Section: Mr Analysismentioning
confidence: 99%
“…Authors found that there was a negative correlation between urinary paraxanthine levels and stroke risk. However, the negative association of urinary caffeine levels with stroke incidence was observed specifically in Mexican Americans, with no evident correlation in other populations, implying potential predictive and diagnostic implications in clinical practice ( 43 ). Another study also based on NHANES database also indicated a U-shaped correlation exists between serum uric acid levels and the risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…We used data from the NHANES for a decade from 2009 to 2018. Using a stratified, multistage probability design, the NHANES provides a representative sample of the non-institutionalized US population ( Zare et al, 2021 , Zare et al, 2021 , Fan et al, 2023 ). We selected adults (age ≥ 20 years) from NHANES 2009–2018 for this research ( Fig.…”
Section: Methodsmentioning
confidence: 99%